Reducing door-to-balloon time in STEMI patients through instant messaging: An empirical study during the COVID-19 pandemic - Yi-Chun Yang; Chih-Tsung Liu; Bao-Tzung Wu (Tungs’ Medical Journal)
Background: Percutaneous coronary intervention (PCI) is the preferred treatment for ST-segment elevation myocardial infarction (STEMI). Guidelines recommend maintaining the door-to-balloon time (DTBT) within 90 min to improve treatment outcomes and minimize complications. However, the coronavirus disease 2019 pandemic has posed additional challenges for the healthcare systems. Objectives: This study aims to evaluate the impact of the LINE instant messaging system on DTBT in STEMI patients, focusing on its role in improving communication between emergency department physicians and catheterization lab personnel. Methods: This retrospective study analyzed data from STEMI patients hospitalized in a regional hospital in central Taiwan. Patients were categorized into a control group (2020–2021, standard care) and an experimental group (2022–2023, care enhanced with LINE instant messaging). Medical records were retrospectively reviewed and analyzed. Results: A total of 269 STEMI patients were included (experimental group: 129 and control group: 140). The proportion of patients achieving door-to-electrocardiogram time (DTET) ≤10 min was similar in the two groups (experimental: 92.2% and control: 93.6%; P = 0.674). Similarly, there was no significant difference in DTBT ≤90 min (experimental: 78.9% and control: 78.6%; P = 0.956) or discharge outcomes (experimental: 3.1% and control: 2.1%; P = 0.624). Conclusion: DTBT ≤90 min was positively correlated with DTET ≤10 min (r = 0.244, P < 0.01) and door-to-catheter room time (DTCT; r = 0.461, P < 0.01). The use of LINE instant messaging streamlined emergency room communication and reduced inefficiencies, but uncontrollable factors during the pandemic continued to affect PCI times. This study highlights the potential of instant messaging to improve DTBT in STEMI patients.